Developing Flashcard Games to Teach Speaking Skill for Islamic Vocational High School Students - A, Sevril Kurnia; Saifudin, Ahmad Saifudin; Widiarini, Widiarini; Makrifah, Istina Atul Makrifah Atul (Jurnal Pembelajaran dan Ilmu Pendidikan, 2025)
This research aims to create interesting learning materials to teach speaking skills to tenth-grade students at SMK Islam 1 Blitar. Traditional English teaching approaches sometimes fail to engage students and promote active speaking, resulting in minimal development. The study proposes using the Flashcards game for language learning to address this issue. The game promotes vocabulary mastery, speaking confidence, and active engagement. The game's effectiveness was evaluated through research and development, including a trial with 38 students. The Flashcards game considerably improved learning, with a questionnaire score of 81.4%, indicating validity. The evaluation showed that the game is an effective teaching tool. Research shows that interactive games, such as Flashcards, can improve students' speaking skills and create an interesting learning environment. This technique aligns with modern education trends that prioritize interactive, student-centered learning. In conclusion, the Flashcards game effectively improves speaking skills and student motivation.